The Long-Run Effects of America’s Largest Residential Racial Desegregation Program: Gautreaux - Chyn, Eric; Collinson, Robert; Sandler, Danielle H (Quarterly Journal of Economics, 2025)
ABSTRACT This article studies the effects of the largest residential racial desegregation initiative in U.S. history, the Gautreaux Assisted Housing Program. From the late 1970s to the 1990s, Gautreaux moved thousands of Black families into predominantly white neighborhoods to support racial and economic integration. We link historical program records to administrative data and use plausibly exogenous variation in neighborhood placements to study how desegregating moves affect children in the long run. Being placed in the predominantly white neighborhoods targeted by the program significantly increases children’s future lifetime earnings and wealth. These moves also increase the likelihood of marriage and particularly raise the probability of being married to a white spouse. Moreover, placements through Gautreaux affect neighborhood choices in adulthood. Those placed in predominantly white neighborhoods during childhood live in more racially diverse areas with higher rates of upward mobility nearly 40 years later.